Teologiczne i świeckie znaczenia pojęcia misje w polskich nowych mediach Ich przeobrażenia w czasie - Wrzos, Marcin (Annales Missiologici Posnanienses, 2019)
The turn of the 20 th and 21 st centuries is connected with the significant development of the technology of social media. This is the period when the so-called new media that have a significant impact on building religious awareness of modern societies. This article is a record of research on the meanings of the concept of mission in new media, as well as the extent to which these meanings have changed over time, from ancient periods to the present day. The author presents changes in the scope of the meaning of the term missions and shows his contemporary meanings that are present in new media: entertainment, political, business, cosmic, vocational, diplomatic, automotive, health or sports. The concept of missions in the Christian field occurs in around 13%. The author makes a statement of this fact, to what extent it is the result of the secularization of society, and how much of a positive process of implementing the concept of missions into a broader linguistic range of meaning, or both.